2022
DOI: 10.1021/acsbiomaterials.1c01259
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Fiducial Markers for Bimodal Near-Infrared Fluorescence- and X-ray-Based Imaging

Abstract: This study aimed to evaluate, for the first time, implantable, biodegradable fiducial markers (FMs), which were designed for bimodal, near-infrared fluorescence-based (NIRF) and X-ray-based imaging. The developed FMs had poly­(l-lactide-co-caprolactone)-based core–shell structures made of radiopaque (core) and fluorescent (shell) composites with a poly­(l-lactide-co-caprolactone) matrix. The approved for human use contrast agents were utilized as fillers. Indocyanine green was applied to the shell material, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…In this study, we proposed a novel composite for fiducial marker fabrication, which is compatible with both NIRF‐ and X‐ray‐based imaging which was compared with reference materials reported previously 11 . The composite, PHXG, is composed of 10 wt% of iohexol, 20 wt% of HAp in P[LAcoCL] matrix and a NIR dye, ICG, which content was tested in the range of 0.0001–0.01 wt%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we proposed a novel composite for fiducial marker fabrication, which is compatible with both NIRF‐ and X‐ray‐based imaging which was compared with reference materials reported previously 11 . The composite, PHXG, is composed of 10 wt% of iohexol, 20 wt% of HAp in P[LAcoCL] matrix and a NIR dye, ICG, which content was tested in the range of 0.0001–0.01 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the ability to emit the fluorescence in the NIR range, the developed material absorbs the X‐ray radiation – it is radiopaque. In our recent work, 11 long‐term X‐ray‐based contrasting properties of PX and PXH composites were assessed in vitro and in vivo. We reported that in the presence of HAp, the release of iohexol was accelerated, which was determined indirectly by measuring changes in intensity of reconstructed images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, ICG@ PSMA nanoagents exhibit strong NIR fluorescence as well as reduced systemic toxicity for cervical cancer cells (Chen et al, 2021). Also, ICG can be encapsulated into other synthetic polymers to perform NIR imaging, including PLGA (Choi et al, 2021), polyethylene glycol (PEG) (Wang et al, 2022b), polymeric nanomicelles (PNMs) (Hsu et al, 2020), poly (allylamine hydrochloride) (PAH) (Bahmani et al, 2014), poly caprolactone (PCL) (Chien et al, 2018;Gorecka et al, 2022).…”
Section: Figurementioning
confidence: 99%